2010
DOI: 10.3109/s10165-009-0246-1
|View full text |Cite
|
Sign up to set email alerts
|

Raised concentration of soluble form of vascular endothelial cadherin and IL-23 in sera of patients with Behçet’s disease

Abstract: Behçet's disease (BD) is a chronic multisystem vasculitis disease that can affect any organ and usually is combined with hyperactivation of neutrophils. Involvement of inflammatory cytokines such as interleukin (IL)-12 in BD has been shown before. However, IL-12 shares a p40 subunit with IL-23, which has additional inflammatory effects apart of IL-12. IL-23 increases neutrophils' transmigration and therefore could contribute in BD induction or progression. Moreover, endothelial cells express vascular endotheli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 23 publications
1
14
0
Order By: Relevance
“…Ustekinumab is a humanized monoclonal antibody against interleukin 12 (IL‐12) and IL‐23 . IL‐23 is critical for the differentiation of Th17 lymphocytes, and previous studies have demonstrated the key role of Th1 and Th17 in the pathogenesis of BD and the correlation of these cytokines with disease activity . Genome‐wide association studies conducted in Japan and Turkey showed IL23R and IL12RB2 loci variations to be associated with BD .…”
Section: Introductionmentioning
confidence: 99%
“…Ustekinumab is a humanized monoclonal antibody against interleukin 12 (IL‐12) and IL‐23 . IL‐23 is critical for the differentiation of Th17 lymphocytes, and previous studies have demonstrated the key role of Th1 and Th17 in the pathogenesis of BD and the correlation of these cytokines with disease activity . Genome‐wide association studies conducted in Japan and Turkey showed IL23R and IL12RB2 loci variations to be associated with BD .…”
Section: Introductionmentioning
confidence: 99%
“…Although the use of the ELISA kit was different from the method used in the previous study , the serum soluble VE‐cadherin levels in the present control subjects were higher than those in the previous study. Outside of sepsis patients, elevated circulating levels of VE‐cadherin have been found in patients with coronary atherosclerosis , cancers , ovarian hyperstimulation syndrome , and Behçet's disease . Among controls in the present study, no patient had ovarian hyperstimulation syndrome, cancers or rheumatic diseases, but it was possible that patients with asymptomatic coronary atherosclerosis could not be fully excluded.…”
Section: Discussionmentioning
confidence: 57%
“…A previous study has shown higher IL-23 in sera of BD patients with uveitis and found that there was a meaningful correlation between IL-23 content and disease activity [3]. Moreover, Lew et al reported an increased expression of IL-23 p19 mRNA in erythema nodosum-like lesions of BD patients [4].…”
mentioning
confidence: 97%